Hukum dan Teknologi: Model Kolaborasi Hukum dan Teknologi dalam Kerangka Perlindungan Hak Cipta di Internet - Budi Agus Riswandi (Fakultas Hukum Universitas Islam Indonesia, 2016)
The main issues in this research include: first, what the legal issues and cases are related to the protection of copyright on internet? Second, how is the development of the copyright protection recently? Third, is the collaboration of law and technology as the model of copyright protection on internet? This research was conducted by using the normative legal method. The result of the research showed some conclusions: first, the presence of internet has brought a negative impact on the attitude and behavior of human. Such negative impact is reflected with the increasing cases of copyright infringement. Therefore, the issue of copyright protection on internet becomes one of crucial issues. Second, recently, the copyright protection on internet can be done through technology approach or legal approach. If these two approaches are conducted separately, then the copyright protection on internet is found very difficult to be realized. To realize the copyright protection, then the model of the collaboration between the technology approach and legal approach becomes something certain. Third, the instrument of the copyright protection in internet collaborates between the technology and legal approach as seen in the regulation in Article 11 and 18 WIPO Internet Treaties and in some other countries such as United States and Indonesia.